2021
DOI: 10.1038/s41467-021-22779-9
|View full text |Cite
|
Sign up to set email alerts
|

Single-keratinocyte transcriptomic analyses identify different clonal types and proliferative potential mediated by FOXM1 in human epidermal stem cells

Abstract: Autologous epidermal cultures restore a functional epidermis on burned patients. Transgenic epidermal grafts do so also in genetic skin diseases such as Junctional Epidermolysis Bullosa. Clinical success strictly requires an adequate number of epidermal stem cells, detected as holoclone-forming cells, which can be only partially distinguished from the other clonogenic keratinocytes and cannot be prospectively isolated. Here we report that single-cell transcriptome analysis of primary human epidermal cultures i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 64 publications
3
55
1
Order By: Relevance
“…Impressive is the change in the morphology of the cells. The keratinocytes onto the “Ma/Col-Ca-polyP-NP” change to a 'cobblestone' pattern, which is characteristic for keratinocytes in the lowermost epidermal cell layer, the stratum basale 33 ; they are the interfollicular epidermis stem cells from where the clonogenic keratinocytes maturate 34 (Figure 3 C and D). In addition and frequently, these cells are covered with numerous microvilli (Figure 3 D).…”
Section: Resultsmentioning
confidence: 99%
“…Impressive is the change in the morphology of the cells. The keratinocytes onto the “Ma/Col-Ca-polyP-NP” change to a 'cobblestone' pattern, which is characteristic for keratinocytes in the lowermost epidermal cell layer, the stratum basale 33 ; they are the interfollicular epidermis stem cells from where the clonogenic keratinocytes maturate 34 (Figure 3 C and D). In addition and frequently, these cells are covered with numerous microvilli (Figure 3 D).…”
Section: Resultsmentioning
confidence: 99%
“…Concerning putative stem cell populations, it seems that spatial location may be more relevant than previously thought, and the authors show the importance of the localization of the different cell populations in relation to epidermal rete ridges. Of note, scRNA-seq analyses of clonogenic keratinocytes in culture showed that the holoclone-forming cells are defined by the expression of FOXM1 gene downstream of YAP [46].…”
Section: Single-cell Analyses Of Keratinocytesmentioning
confidence: 99%
“…Such culture method, first developed by Rheinwald and Green (hereafter R&G) in the mid-1970s, is still regarded as the “gold standard” in clinical settings [ 9 , 10 ]. Notably, R&G conditions do not mimic epidermal homeostasis but rather recapitulate the burst of epidermal regeneration occurring upon wound healing [ 11 ]. Under these conditions, the capacity of individual keratinocyte clones to generate secondary clonogenic cultures can be quantified via morpho-functional clonal analysis.…”
Section: Introductionmentioning
confidence: 99%
“…At the molecular level, holoclones derived from different stratified epithelia, such as the epidermis, the thymic epithelium, and the limbal-corneal epithelium, express elevated levels of the ∆Np63α isoform, a key determinant of keratinocyte cell identity, which is essential for the maintenance of stem cells proliferative potential and survival ability [ 14 , 15 , 16 , 17 ]. A very recent study has further unraveled the transcriptional profiles of human epidermal holoclones at the single-cell level [ 11 ]. Besides possessing elevated p63 levels, holoclone-forming cells selectively express the FOXM1 transcription factor, a YAP target gene required for long-term self-renewal ability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation